KONTRIBUSI MOTIVASI BELAJAR, KREATIVITAS TERHADAP PROBLEM SOLVING (PEMECAHAN MASALAH) SISWA DALAM BELAJAR SERTA IMPLIKASI TERHADAP BIMBINGAN DAN KONSELING DI SMPN 29 PADANG - Nuzliah Nuzliah (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2015)
Problem Solving ability was very crucial to support the students in learning activities. Those who were able to solve learning problems would get satisfactory achievement and vise versa. Problem solving ability of the students was affected by their learning motivation and creativity. This research was intended to reveal the students’ learning motivation, creativity and problem solving ability in learning. In addition this research also sought to reveal the contribution of learning motivation and creativity toward the students’ Problem Solving ability in learning. This research applied correlational approach which was aimed at revealing the extent to which a variable contributed to the other variable in a research. The population of the research was 283 students in class VII of SMP Negeri 29 Padang. By using Proportional Stratified Random Sampling technique, 166 students were chosen as the sample. The instrument of the research was Likert scale model. The data gotten were analyzed by using descriptive technique. The hypothesis was tested by using multiple regression technique. The research findings indicated that: (1) the students’ learning motivation in general was in low category, (2) the students’ creativity in general was in average category, (3) problem solving ability of the students was in average category, (4) learning motivation had contribution toward the students’ problem solving ability in learning (5) creativity had contribution toward the students’ problem solving ability in learning,(6) learning motivation, creativity had contribution toward the students’ problem solving ability in learning.